An Exploratory Study of EFL Students’ Difficulties in Pronunciation at X1 Grade of a Senior High School in Bandung - Putri, Rizka Rahil; Sakina, Rahma; Arifin, Riyadh Ahsanul (JEPAL (Journal of English Pedagogy and Applied Linguistics), 2024)
Pronunciation is a fundamental part of the language-learning process. In order to speak meaningfully in real-world conversations, students require to be able to pronounce word sound properly. This research aims to explore the pronunciation difficulties faced by students of a private senior high school in Bandung and to find out what factors influenced their difficulties in pronunciation. A descriptive qualitative design method is used in this study. To collect the data, three techniques were used including observation, interview, and questionnaires. The findings highlight several difficulties faced by the students, namely substitution errors, voicing errors, difficulties with consonant voiced and unvoiced, and challenges related to stress, rhythm, and intonation patterns are identified as common challenges. These errors and difficulties are influenced by both internal and external factors such as; students' native language, learning environment, types of teachers, and methods applied. The results of this study are essential because they provide language teachers with insight into the elements that influence the pronunciation of English as a foreign language, as well as the opportunity to reflect on their own learning and teaching methods